If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + (-8) = 6 n + -8 = 6 Reorder the terms: -8 + n = 6 Solving -8 + n = 6 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + n = 6 + 8 Combine like terms: -8 + 8 = 0 0 + n = 6 + 8 n = 6 + 8 Combine like terms: 6 + 8 = 14 n = 14 Simplifying n = 14
| (2x+3)+(x-7)=40 | | 7x+5-x=17 | | -1(8n-2)=3+10-30n | | -3x+8+2x=15 | | 15=-3(5x+5) | | 12x-48=30 | | -4(-6x+8)=16 | | y=(-9)-2x | | -5(4t-3)+9t=2t-8 | | 12x-(9x-5)=17 | | 2(x-2)=5(x+3) | | 35n+25=625 | | 20x^3-17x^2+3x=0 | | .9x-6.2=.1 | | n=1.25n+6.25 | | x+(4+32)=32 | | 6x-4(2x+8)=36 | | 3x-9v=5+7v | | 16x+1=13-2x | | 4-3x+5x=6 | | 5x-3=3x-21 | | 49=-7t+(-7) | | 9m-5m+2=4m+2 | | X^2-6X-12X=0 | | 3y=-21+7x | | 2(x+1)(x+4)-(x-2)(x-2)=0 | | 6x+12-8x=20 | | 3*(x+2)-x= | | 15=3(5x+5) | | 12mn+4m+8mn+6m= | | (n-2)180= | | 2v^2+v+64=0 |